2016
DOI: 10.15252/emmm.201606382
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive lung cancer diagnosis by detection ofGATA6andNKX2‐1isoforms in exhaled breath condensate

Abstract: Lung cancer (LC) is the leading cause of cancer‐related deaths worldwide. Early LC diagnosis is crucial to reduce the high case fatality rate of this disease. In this case–control study, we developed an accurate LC diagnosis test using retrospectively collected formalin‐fixed paraffin‐embedded (FFPE) human lung tissues and prospectively collected exhaled breath condensates (EBCs). Following international guidelines for diagnostic methods with clinical application, reproducible standard operating procedures (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 41 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…A recent study suggests that modulating the expression of GATA6 may affect the growth of NSCLC cells ( 27 ). Mehta et al verified GATA6 and NKX2-1 as diagnostic biomarkers of non-invasive lung cancer ( 28 ). BMP4 regulation by GATA6 showed that it can inhibit tumorigenesis and metastasis of lung adenocarcinoma cells ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that modulating the expression of GATA6 may affect the growth of NSCLC cells ( 27 ). Mehta et al verified GATA6 and NKX2-1 as diagnostic biomarkers of non-invasive lung cancer ( 28 ). BMP4 regulation by GATA6 showed that it can inhibit tumorigenesis and metastasis of lung adenocarcinoma cells ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…GATA6 is a member of the GATA transcription regulator family. As a gene that is closely related to the occurrence and development of diseases, it is involved in a variety of biological behaviors of cells and has a significant relationship with the process of different tumors [7][8][9]. Therefore, it is of great importance to fully understand and study the GATA6 gene.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are key regulators of lung development and each one gives rise to two different isoforms: the embryonic isoform (Em) mainly expressed during early developmental stages and the adult (Ad) isoform expressed during the later stages of lung development. These authors proved that Em/Ad expression ratio of GATA6 and NKX2-1 increased in the EBC of lung cancer patients compared with EBC extracted from control subjects, highlighting the potential use of EBC for lung cancer detection [47].…”
Section: Ebc Analysismentioning
confidence: 91%
“…Another type of nucleic acid present in EBC is RNA. There have been no published data on transcriptomics studies on EBC, and very little is known of messenger RNAs present in this biofluid [28] because of the high fragmentation of the RNA isolated from EBC [47].…”
Section: Ebc Analysismentioning
confidence: 99%